Culturally sustaining and revitalizing pedagogies : language, culture, and power - Jimenez-Silva, Margarita; Coulter, Cathy (Bingley, U.K. : Emerald Publishing Limited, 2017)
Today's schools compartmentalize children and curriculum. Standardization dictates curricular content and assessment, narrowing the focus of classrooms and schools that serve diverse populations from varied geographical backgrounds. Against the backdrop of the western-derived, institutional framework of schooling are cultural ways of knowing that are place-based, holistic, experiential, and connected to oral storytelling. In the current movement toward acknowledging and understanding cultural knowledge, teacher education programs need to work in collaboration with cultural communities, honoring traditions and epistemologies and seeking to revitalize and sustain (Paris, 2012) language and culture. Such initiatives inform the big picture of educational reform and enrich mainstream university teacher education programs. This book highlights the journeys, challenges and unfolding stories of transformation that reside within university/community/school partnerships focused on cultural and linguistic revitalization through schooling.
Prelims -- Introduction -- Power -- Culture -- Language -- About the authors -- Index.
Includes bibliographical references and index.
Keywords: Culturally relevant pedagogy; Language and culture; Education -- Teaching Methods & Materials -- General; Teaching skills & techniques